2020
DOI: 10.1111/clr.13659
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation around unstable implants is enhanced by a WNT protein therapeutic in a preclinical in vivo model

Abstract: Objectives Our objective was to test the hypothesis that local delivery of a WNT protein therapeutic would support osseointegration of an unstable implant placed into an oversized osteotomy and subjected to functional loading. Materials and methods Using a split‐mouth design in an ovariectomized (OVX) rat model, 50 titanium implants were placed in oversized osteotomies. Implants were subjected to functional loading. One‐half of the implants were treated with a liposomal formulation of WNT3A protein (L‐WNT3A); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…At day 14, all peri-implant cells showed evidence of osteogenic differentiation and mineralization. At the same time point, lateral stability testing confirmed that the L-Wnt3A treated cases have stiffer interface than the control group [89].…”
Section: Wnt Pathway and Different Biological Responses Of Bone Typesmentioning
confidence: 79%
“…At day 14, all peri-implant cells showed evidence of osteogenic differentiation and mineralization. At the same time point, lateral stability testing confirmed that the L-Wnt3A treated cases have stiffer interface than the control group [89].…”
Section: Wnt Pathway and Different Biological Responses Of Bone Typesmentioning
confidence: 79%
“…The animals were allowed to heal, and 3 months later, the oversized osteotomies were prepared, and implants placed. This model has been used in different animal models and with different materials (Coelho et al, 2013; Coyac et al, 2020; Lima Bueno et al, 2020). In the case of the negative control (no material around the implant) or the implants with bone xenograft around them, the implant was placed in the osteotomy first.…”
Section: Methodsmentioning
confidence: 99%
“…The early stage of bone repair response after dental implant insertion is a complex phenomenon in which the combined action of inflammatory cascade and immune system regulate new bone formation and neo‐angiogenesis 1 . Among various factors influencing the healing process, excessive implant micro‐movement may compromise osseointegration by producing large interfacial strains which, especially in low‐quality bone, induce bone resorption and determine fibrous encapsulation of the fixture 2–4 . Therefore, one of the main goals in implant surgery is the achievement of adequate primary stability, which is strictly related to both bone quality and quantity, implant design, and implant site preparation characteristics 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Among various factors influencing the healing process, excessive implant micro‐movement may compromise osseointegration by producing large interfacial strains which, especially in low‐quality bone, induce bone resorption and determine fibrous encapsulation of the fixture. 2 , 3 , 4 Therefore, one of the main goals in implant surgery is the achievement of adequate primary stability, which is strictly related to both bone quality and quantity, implant design, and implant site preparation characteristics. 5 Implant bed preparation should be performed with minimal trauma to the bone, avoiding overheating, and excessive compression of the cortical layer to prevent an excessive inflammatory phase potentially causing massive bone resorption, delayed healing or implant failure.…”
Section: Introductionmentioning
confidence: 99%